Relationship between genetic knowledge and familial communication of CRC risk and intent to communicate CRCP genetic information: insights from FamilyTalk eMERGE III. Issue 2 (24th June 2020) - Makhnoon, Sukh; Bowen, Deborah J; Shirts, Brian H; Fullerton, Stephanie M; Meischke, Hendrika W; Larson, Eric B; Ralston, James D; Leppig, Kathleen; Crosslin, David R; Veenstra, David; Jarvik, Gail P
Abstract: Successful translation of genetic information into patient-centered care and improved outcomes depends, at least in part, on patients' genetic knowledge. Although genetic knowledge is believed to be an important facilitator of familial communication of genetic risk information, empirical evidence of this association is lacking. We examined whether genetic knowledge was related to frequency of current familial communication about colorectal cancer and polyp (CRCP) risk, and future intention to share CRCP-related genomic test results with family members in a clinical sample of patients. We recruited 189 patients eligible for clinical CRCP sequencing to the eMERGE III FamilyTalk randomized controlled trial and surveyed them about genetic knowledge and familial communication at baseline. Participants were primarily Caucasian, 47% male, average age of 68 years, mostly well educated, and with high-income levels. Genetic knowledge was positively associated with future-intended familial communication of genetic information (odds ratio = 1.11, 95% confidence interval: 1.02–1.23), but not associated with current communication of CRC risk (β = 0.01, p = .58). Greater current communication of CRC risk was associated with better family functioning (β = 0.04, p = 8.2e-5). Participants' genetic knowledge in this study was minimally associated with their intended familial communication of genetic information. Although participants have good intentions of communication, family-level factors may hinder actual follow through of these intentions. Continued focus on improving proband's genetic knowledge coupled with interventions to overcome family-level barriers to communication may be needed to improve familial communication rates.